Kegiatan Literasi pada Ibu PKK Dusun Bendan Sawangan Magelang dalam Rangka Meningkatkan Penggunaan Obat secara Rasional - Widarika Santi Hapsari; Fitriana Yuliastuti; Alfian Syarifuddin; Ni Made Ayu Nila Septianingrum (Jurnal Pemberdayaan Masyarakat, 2020)
Self-medication activities are part of the community's efforts to take care of their health. Gevaarlijk and antibiotics are types of drugs that can only be obtained by prescription from a doctor. Both types of these drugs should not be stored because their use must be under the supervision and has the potential to cause bacterial resistance related to the use of antibiotics. Based on Riskesdas 2013, there are still many people who store gevaarlijk and antibiotics for self-medication. This shows the irrational use of drugs. Community service activities aim to improve knowledge and skills in the use of rational medicine. The method used is the Community-Based Interactive Approach method in which participants play an active role in activities. This participation is important to practice the ability and skill in solving problems. Activities carried out through counseling about the use of rational drugs and antibiotics, then continued with training and assistance for the rational use of drugs and antibiotics. End result of this activity is expected that the community will be able to apply rational drug use and disseminate this information to the wider community.